Comparison of morphometric traits and condition index of freshwater mussel Lamellidens marginalis (Lamarck, 1819) populations across three ecologically distinct habitats of Bangladesh (Journal of the Bangladesh Agricultural University, 2026)
Morphological variation is a fundamental component of taxonomic research and provides critical insights into population-level biological and ecological differentiation. The present study investigated inter-population morphological variability in the freshwater mussel Lamellidens marginalis collected from three ecologically distinct freshwater habitats from North Central Bangladesh. Specimens (n = 100 per site) were sampled from Darikathal Beel, Trishal, Mymensingh (S1); the Old Brahmaputra River near the Botanical Garden, Bangladesh Agricultural University, Mymensingh (S2); and a pond adjacent to Boali Jam-E-Masjid, Tangail (S3) during December 2023. Twenty-three morphometric, mass-related, and derived ratio parameters were analyzed, including shell dimensions, soft tissue traits and proportional indices. Statistical comparisons revealed significant differences (p < 0.05) in 19 of the 23 parameters among at least two populations, indicating pronounced habitat-associated morphological divergence. Shell proportional indices demonstrated clear habitat-specific patterns. The SL/SH ratio indicated greater shell elongation in riverine population compared to the beel population. Conversely, ST/SH and SL/ST ratios suggested that pond-dwelling mussels possessed comparatively rounder and thinner shells than those from beel and riverine habitats. Condition index differed significantly (p < 0.05) between riverine and beel populations, reflecting a gradient of habitat suitability ranked as river > pond > beel. Overall, the findings highlight the strong influence of habitat-specific environmental conditions on shell morphology and physiological condition in L. marginalis. These results underscore the importance of integrating morphological assessments with molecular genetic analyses to achieve a more robust understanding of population structure and taxonomic resolution of L. marginalis across heterogeneous freshwater ecosystems in Bangladesh.J Bangladesh Agril Univ 24(2): 157–166, 2026